Antimicrobial, Antioxidant, and Anti-Inflammatory Properties of Monofloral Honeys from Chile - Erick Poulsen-Silva; Felipe Gordillo-Fuenzalida; Patricia Velásquez; Felipe M. Llancalahuen; Rodrigo Carvajal; Mauricio Cabaña-Brunod; María Carolina Otero (MDPI AG, 2023)
Honey is a mixture of compounds produced by bees that has been appreciated by humanity since the creation of the oldest civilizations. It has multiple uses and can be a highly nutritional and healing substance. It has been used in traditional medicine as a natural alternative for the treatment of diverse clinical conditions. This is due to its reported bioactive properties. The objective of this article is to exhibit and analyze the biological properties of different types of honey originating from Chile based on their antimicrobial, antioxidant, and anti-inflammatory activities, focusing primarily on recompiling experimental studies made on monofloral honey of plant species present in the Chilean territory. The result of this bibliographical review shows that Chilean honey possesses remarkable bioactive properties, mainly antimicrobial and antioxidant activities, with a few studies on its anti-inflammatory activity. Most of these results were attributed to monofloral honey belonging to ulmo (Eucryphia cordifolia) and quillay (Quillaja saponaria Molina) plant species. These properties are related to the presence of several bioactive components, such as phenolic components (mainly flavonoids), hydrogen peroxide (H2O2), enzymes, proteins, and carbohydrates. The biodiversity of the flora and the environmental conditions of the Chilean territory are responsible for the wide range of bioactive compounds and biological properties found in Chilean honey. Further studies must be made to uncover the medicinal potential of these native honeys.